Implications of the use of mechanical thrombectomy on outcome in large vessel occlusion following the 2015 landmark trials. (7th May 2020) - Kuybu, Okkes; Javalkar, Vijayakumar; Amireh, Abdallah; Kaur, Arshpreet; Kelley, Roger E; Cuellar-Saenz, Hugo H; Sharma, Pankaj
Abstract : Background: The effectiveness of mechanical thrombectomy (MT) was demonstrated in five landmark trials published in2015.Mechanical thrombectomy is now standard of care for acute ischemic stroke and has been growing in popularity after publication of landmark trials. Objective: To analyze outcomes and trends of the use of MT and intravenous thrombolysis (IVT) in patients with acute ischemic stroke in US hospitals before and after publication of these trials. Methods: Patients discharged with a diagnosis of ischemic stroke between 2012 to 2017 were diagnosed using ICD codes from the National Inpatient Sample. Thereafter, patients given acute stroke treatment were identified using the corresponding procedure codes for IVT and MT. The primary clinical outcomes of in-hospital mortality and disability were then compared between two time periods: 2012–2014 (pre-landmark trials) and 2015–2017 (post-landmark trials). Binary logistic regression and Χ 2 tests were used for statistical analysis. Results: A total of 57 675 patients (median age 68.9 years (range 18-90), 50.1% female) were identified with acute procedures. Of these patients, 57.6% were from the post-landmark trials time period. Despite an increased number of cases, the rate of IVT decreased from 84.3% to 75.9% and the rate of IVT+MT decreased from 7.1% to 6.3%. After publication of the pivotal trials in 2015, the rates of MT increased from 8.7% to 17.8%. Significant reductions of in-hospital mortality (7.1% vs 8.7%, p<0.001) and disability (64% vs 66.2%, p<0.001) were noted. Conclusion: The analysis showed a significant increase in the proportion of patients receiving MT after 2015. This has translated into reduction of in-hospital mortality and improvement in disability.